2020
DOI: 10.3389/fgene.2020.00727
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Bioinformatics Approaches to Screen Potential Prognostic Immune-Related Genes and Drugs in the Cervical Cancer Microenvironment

Abstract: In developing countries, cervical cancer is still the major cause of cancer-related death among women. To better understand the correlation between tumor microenvironment (TME) and prognosis of cervical cancer, we screened 1367 differentially expressed genes (DEGs) of cervical cancer samples in The Cancer Genome Atlas (TCGA) database using Estimation of STromal and Immune cells in MAlignant Tumor tissues using Expression data (ESTIMATE) algorithm-derived immune scores. Then, we extracted 401 tumor immune micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 75 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…In this study, we attempted to establish a predictive model with four immune-related genes with an expression matrix of 1-or-2 to replace their previous specific expression values. To a certain extent, we avoided the problem caused by platform differences and detecting technique to a certain extent, so as to make up for the limitations of previous studies (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we attempted to establish a predictive model with four immune-related genes with an expression matrix of 1-or-2 to replace their previous specific expression values. To a certain extent, we avoided the problem caused by platform differences and detecting technique to a certain extent, so as to make up for the limitations of previous studies (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated the underlying mechanisms of CC, particularly with regard to the TME, therapeutic targets, and prognostic factors ( Che et al, 2020 ; Lu et al, 2020 ; Zhao et al, 2020 ). However, the current understanding remains unsatisfactory and insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current understanding remains unsatisfactory and insufficient. Numerous previous research studies concentrated mainly on the RNA-seq profiles, which are characterized by some disadvantages in comprehensively clarifying the potential mechanisms involved ( Sun et al, 2019 ; Liu et al, 2020 ; Ma J. et al, 2020 ; Zhao et al, 2020 ; Yang et al, 2021 ). Many researchers have recently concentrated on investigating prognostic factors by integrative multi-omics data analysis, which yielded more powerful results and provided a more comprehensive view of the TME ( Gu et al, 2020 ; Ma H. et al, 2020 ; Yan et al, 2020 ; Zhang Y. et al, 2020 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the immune component seems to contribute more to immunotherapy-response of CC, including the T cells, macrophages, and neutrophils ( Langers et al, 2014 ; Krishnan et al, 2018 ; Chen X. J. et al, 2019 ; Ohno et al, 2020 ). Many researchers have currently investigated the correlation of the prognosis in CC patients with the critical immunological biomarkers ( De Jaeghere et al, 2020 ; Yuan et al, 2020 ; Zhao et al, 2020 ). These studies showed significant heterogeneity of the immune component and immune response in CC patients, which might play a decisive role in the ultimate clinical outcomes of patients.…”
Section: Introductionmentioning
confidence: 99%